2016
DOI: 10.3201/eid2203.151006
|View full text |Cite
|
Sign up to set email alerts
|

Highly Pathogenic Avian Influenza A(H5N8) Viruses Reintroduced into South Korea by Migratory Waterfowl, 2014–2015

Abstract: Highly pathogenic avian influenza A(H5N8) viruses were isolated from migratory waterfowl in South Korea during fall 2014–winter 2015, a recurrence after initial introduction in winter 2014. These reappeared viruses were phylogenetically distinct from isolates circulating in poultry farms in South Korea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 14 publications
1
33
0
Order By: Relevance
“…Clade 2.3.4.4A viruses have been detected from various species of wild birds including apparently healthy wild birds (Jeong et al., ; Kwon et al., ), leading to the hypothesis that the clade 2.3.4.4A virus was disseminated from East Asia to North America by circulation and relay transmission via long‐distance migratory birds passing through the Beringia region, such as Northern Pintail (Global Consortium for H5N8 and Related Influenza Viruses, ; Lee et al., ). Our findings support this hypothesis because H5N8/15 virus efficiently replicated and was shed from respiratory and intestinal tracts and transmitted between Northern Pintail without causing illness or death.…”
Section: Resultsmentioning
confidence: 99%
“…Clade 2.3.4.4A viruses have been detected from various species of wild birds including apparently healthy wild birds (Jeong et al., ; Kwon et al., ), leading to the hypothesis that the clade 2.3.4.4A virus was disseminated from East Asia to North America by circulation and relay transmission via long‐distance migratory birds passing through the Beringia region, such as Northern Pintail (Global Consortium for H5N8 and Related Influenza Viruses, ; Lee et al., ). Our findings support this hypothesis because H5N8/15 virus efficiently replicated and was shed from respiratory and intestinal tracts and transmitted between Northern Pintail without causing illness or death.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, two HPAI H5N2 viruses were noted to acquire distinct mammalian adaptive markers, either PB2 E627K34 or D701N35 in mice. A recent surveillance studies suggested that H5N8 viruses isolated during each outbreak were phylogenetically distinct3136, suggesting that minor genetic differences between the 2 viruses potentially resulted in distinctive selection of adaptive markers; however, further study will be needed to test these hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…These groups were included among the H5N8 viruses that spread to Europe, Japan, and Taiwan after further evolution in the breeding sites of migratory birds [2910]. The viruses were also introduced into poultry farms and circulated for 4–5 months in South Korea (panel B in Fig.…”
mentioning
confidence: 99%